1972
DOI: 10.2136/sssaj1972.03615995003600030034x
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration Rate as Affected by Soil Freezing Under Three Cover Types

Abstract: Infiltration rate in a frozen Fayette silt loam soil under contiguous areas of natural deciduous forest, 25‐year‐old confierous plantation, and 6‐year‐old abandoned field vegetation was measured over the winter of 1969‐70 using tin can infiltrometers and a water‐ethylene glycol solution. The deciduous forest site had a natural soil profile; the conifer plantation and abandoned field sites were once cultivated. Prefreeze infiltration rate was similar for all cover conditions. In deciduous forest and abandoned f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Initial work by Post and Dreibelbis (1942) showed that frost penetration increased as vegetation type changed, from woodland through meadow pasture to wheat (Triticum aestivum), for sites in Ohio, USA. A related pattern was also observed by Harris (1972), who compared coniferous, deciduous, and open field sites at thaw and reported that the coniferous plantation remained frozen longer.…”
Section: A Ground Coversupporting
confidence: 68%
“…Initial work by Post and Dreibelbis (1942) showed that frost penetration increased as vegetation type changed, from woodland through meadow pasture to wheat (Triticum aestivum), for sites in Ohio, USA. A related pattern was also observed by Harris (1972), who compared coniferous, deciduous, and open field sites at thaw and reported that the coniferous plantation remained frozen longer.…”
Section: A Ground Coversupporting
confidence: 68%
“…The existence of an inverse relationship between infiltration and frozen soil moisture has been demonstrated or postulated by many investigators (Willis et al 1961;Kuzik and Bezmenov 1963;Gillies 1968;Shipak 1969;Romanov et al 1974;Motovilov 1979;Granger and Dyck 1980;Kane 1980). Haupt (1967) and Harris (1972) have demonstrated the effect of different types of frost, as well as the number and orientation of connected macropores, on the absorption of meltwater.…”
Section: Review Of Factors Affecting Snowmelt Infiltrationmentioning
confidence: 87%
“…In agricultural areas, erosion from a partially thawed soil surface can be excessive. However, the infiltration capacity through soils that are initially dry or have large macropores is often minimally affected by soil freezing (Harris, 1972). The thick litter layer and large macropores found in typical forest soils minimize the potential effects of soil freezing on infiltration (Lutz and Chandler, 1946).…”
Section: Infiltration-excess Runoffmentioning
confidence: 99%